Bacteraemia and infective endocarditis with Streptococcus bovis-Streptococcus equinus-complex: a retrospective cohort study. Issue 10 (3rd October 2022) - Öberg, Jonas; Nilson, Bo; Gilje, Patrik; Rasmussen, Magnus; Inghammar, Malin
Abstract: Background: Streptococcus bovis/equinus complex (SBSEC) comprise several species and subspecies and is a common cause of infective endocarditis (IE). S. gallolyticus subsp. gallolyticus ( Sg gallolyticus ) accounts for a majority of SBSEC IE, but the risk of IE for other subspecies is largely unknown. We aimed to investigate the clinical presentation of bacteraemia, and proportion of patients with IE in bacteraemia with the most common subspecies. Methods: A retrospective cohort study of SBSEC-bacteraemia identified in clinical laboratory databases, in Skåne Region, Sweden, 2003–2018. Bacteraemia with Sg gallolyticus, S. gallolyticus subsp. pasteurianus ( Sg pasteurianus ), S. lutetiensis and S. infantarius subsp. infantarius ( Si infantarius ) were included. Subspecies was identified by whole genome sequencing. Medical charts were reviewed according to a predetermined protocol, IE was defined by the criteria from European Society of Cardiology. Results: In total, 210 episodes of SBSEC-bacteraemia were included. Definite IE was identified in 28/210 (13%) episodes. Of these, 7/28 (25%) were prosthetic valve-IE, 1/28 (4%) related to a cardiovascular implantable electronic device and 10/28 (36%) required heart valve surgery. The proportions of IE among different subspecies were: Sg gallolyticus 17/52 (33%), Si infantarius 5/31 (16%), Sg pasteurianus 4/83 (5%) and S. lutetiensis 2/44 (5%) ( p  < 0.001). Sg pasteurianus and S. lutetiensis were more often associated with intra-abdominal- and polymicrobial infection. Conclusion: The proportion of IE in SBSEC-bacteraemia varies substantially depending on subspecies. Echocardiography should always be considered in bacteraemia with Sg gallolyticus and Si infantarius, and can sometimes be omitted in bacteraemia with Sg pasteurianus and S. lutetiensis .